"Iron buddies" (safety iron system) / Aisyah Mohd Khaidir...[et al.] - Mohd Khaidir, Aisyah; Zainuddin, Haziqah; Mohd Nasir, Illy Hazirah (2015)
Malaysian citizen today realize how much important it is to have a home that is safe to them and their children. In order to do that, many system have been created to helps people to make sure their home is the best place to live. But, very few people realize that the everyday tools and equipment that they use itself can actually be their enemy and potentially harm them. To prevent the equipment to be harmful, lots of company have created new safety system in their product. But not all product have safety precaution inside their product. This is a disadvantage to the users that love to use their favourite product in daily. As we all know, standard procedure for every product is to go through the inspection and test by SIRIM to make sure that the product is safe. The product safety is not enough to make sure there is no human mistake that will brings problem inside the house. A clever system is needed to be a reminder for human to be more alert to their home surrounding. Our product is simply a device that can be attached to the iron and alert the user if the user left the iron in standing mode for too long. Around a few minutes of time, "Iron Buddies" will then produce an alarming sound so that the user or other people will notice it, so it will remind them that they have left their iron in dangerous position that can potentially be harmful for children and other human.